Clinical Cases in Infectious Diseases : A Public Health Approach - Senanayake, Sanjaya (Sydney McGraw-Hill, 2007)
Infectious diseases do not recognize geographic, political or social boundaries. This book increases our understanding of the synergy generated by these groups when they work closely together to fight notifiable infections.
Keywords: Public health